Penilaian Risiko Menggunakan Metode Hazard Identification Risk Assesment and Determining Control (HIRADC) pada Petugas di IGD & IPLS RSUD Meuraxa Tahun 2025 - Fikri Taufiqurrahman; Tahara Dilla Santi; Dedi Andria (INSOLOGI: Jurnal Sains dan Teknologi, 2026)
The hospital work environment, particularly the Emergency Department (ER) and the Sanitation Waste Management Department (IPLS), has various potential hazards that can threaten the safety of staff. This study aims to identify potential hazards, assess risk levels, and determine occupational risk controls using the HIRADC method at Meuraxa Regional General Hospital. This quantitative study with a descriptive observational approach used a facility observation checklist and semi-structured interviews with staff. Data collection was conducted from June 1–16, 2025, through observation, documentation, and interviews. Risk analysis was based on likelihood and severity, then classified into low, medium, and high risks. The results showed a higher risk of infectious diseases among ER staff (57.1%) compared to ER staff (28.6%). In the ER, moderate–high risks were found in unfastened oxygen cylinders, dusty defibrillators, dirty suction pumps and HFNCs, and portable X-rays without radiation protection. Dominant risks included needlesticks, infection exposure, ampule injuries, limited PPE, noise, aggressive patients, and confined spaces. At the IPLS, high risks are found in the electrical panels and water pumps, and moderate risks are found in the filters and storage areas. The HIRADC method is considered effective and needs to be supported by strengthened controls, OHS training, and strict SOPs.